Organoleptic Quality of Semprit Cookies Made from Yellow Corn Flour (Zea Mays L.) - Vries, Renatha Marcel Emmanuella de; Rumadana, I Made; Hardina, Hardina (Indonesian Journal of Applied and Industrial Sciences (ESA), 2024)
The purpose of this study was to determine the quality produced by semprit cookies made from yellow corn flour. The data collection methods used were experiments, documentation, organoleptic tests, questionnaires, panelist tests, and Likert scales. This study focused on quality tests using the five senses, through experiments in making semprit cookies made from yellow corn flour. After the experiment, it was continued with a panelist test to obtain the results of the quality test from 25 fairly trained panelists. The results obtained from the quality test were 93.6% on the Likert scale for taste, aroma, texture and color. These results are classified as very good criteria. From this study it can be concluded that semprit cookies made from yellow corn flour can be an alternative processed snack for gluten intolerant users.